2016
DOI: 10.1021/acs.est.6b02019
|View full text |Cite
|
Sign up to set email alerts
|

Iron Isotope Fractionations Reveal a Finite Bioavailable Fe Pool for Structural Fe(III) Reduction in Nontronite

Abstract: We report on stable Fe isotope fractionation during microbial and chemical reduction of structural Fe(III) in nontronite NAu-1. (56)Fe/(54)Fe fractionation factors between aqueous Fe(II) and structural Fe(III) ranged from -1.2 to +0.8‰. Microbial (Shewanella oneidensis and Geobacter sulfurreducens) and chemical (dithionite) reduction experiments revealed a two-stage process. Stage 1 was characterized by rapid reduction of a finite Fe(III) pool along the edges of the clay particles, accompanied by a limited rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…7,11,25 For example, previous studies have indicated that biologically reduced NAu-1 results in the reduction of edge-site Fe(III) species and the formation of, mostly, sorbed Fe(II) with limited structural Fe(III) reduction. 23,25,26 When smectites are chemically reduced, however, a greater amount of structural Fe(III) reduction can occur. 23,25,26 Spectroscopic evidence has linked this to the ability of chemical reductants to penetrate the clay surface via the basal plane combined with their very low reduction potential.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,11,25 For example, previous studies have indicated that biologically reduced NAu-1 results in the reduction of edge-site Fe(III) species and the formation of, mostly, sorbed Fe(II) with limited structural Fe(III) reduction. 23,25,26 When smectites are chemically reduced, however, a greater amount of structural Fe(III) reduction can occur. 23,25,26 Spectroscopic evidence has linked this to the ability of chemical reductants to penetrate the clay surface via the basal plane combined with their very low reduction potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23,25,26 When smectites are chemically reduced, however, a greater amount of structural Fe(III) reduction can occur. 23,25,26 Spectroscopic evidence has linked this to the ability of chemical reductants to penetrate the clay surface via the basal plane combined with their very low reduction potential. 27,28 In this study we have examined the ability of Fe(III)-smectite clay mineral suspensions to reduce contaminants in the presence of added aqueous Fe(II) at pH 7.8, as these conditions favor Fe(II) sorption to edge-sites 22 which reflects the clay surface that microbes target for Fe(III)-smectite reduction.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, micro-XANES spectra from the dryland PCA + and PCA – rhizospheres (groups 1, 3, 4, and 5 in Figures , , and S3) did not differ consistently, indicating that the PCA + strain did not alter the identity of Fe-bearing minerals in the dryland rhizospheres. Prior work has demonstrated that extensive electron transfer and atom exchange can occur at the surfaces of Fe­(III)-bearing minerals without causing changes in aqueous Fe­(II) concentrations or mineral identity. ,,,,, In particular, the formation of secondary minerals during DIR is inhibited by the complexation and coprecipitation of Fe with organic matter, including the extracellular polymeric substances found in biofilm matrices. ,,,, …”
Section: Resultsmentioning
confidence: 99%